Topological one-way fiber of second Chern number - Ling Lu (Nature Portfolio, 2018)
Topological one-way fibers are promising candidates for novel fiber devices. Here, Lu et al. propose that one-way fiber modes are topologically protected by the second Chern number in a four-dimensional parameter space, which develop in a helically-modulated magnetic Weyl photonic crystal.